Potensi Destruktif dari Kemalasan - Yosiana Limiati Baitanu; Romelus Blegur; Nastiti Puspita Rini (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), 2022)
Laziness is a lifestyle that no one wants, because it disrupts ethical discourse in the work culture. The aim of this research is to investigate the issue of laziness in relation to the Christian work ethic by referring to the biblical text, namely Proverbs 18:9 which shows a bad precedent for God's decrees for His human creation. The research method used is hermeneutics or biblical interpretation in order to find the meaning of the text for the current context. Related to this, the author uses primary books for exegetical studies, as well as other supporting sources from books and journal articles. The results of this research are that laziness has the potential to be destructive and is contrary to the Christian work ethic which was originally established by God to be passed down from generation to generation in the history of human life. Laziness never brings benefits in any form because its nature is to damage figures that give the image of a lazy character.